The Lymphotoxin β Receptor Is Essential for Upregulation of IFN-Induced Guanylate-Binding Proteins and Survival after Toxoplasma gondii Infection. (6th August 2017) - Behnke, Kristina; Sorg, Ursula R.; Gabbert, Helmut E.; Pfeffer, Klaus
Abstract : Lymphotoxin β receptor (LT β R) signaling plays an important role in efficient initiation of host responses to a variety of pathogens, encompassing viruses, bacteria, and protozoans via induction of the type I interferon response. The present study reveals that after Toxoplasma gondii infection, LT β R −/− mice show a substantially reduced survival rate when compared to wild-type mice. LT β R −/− mice exhibit an increased parasite load and a more pronounced organ pathology. Also, a delayed increase of serum IL-12p40 and a failure of the protective IFN γ response in LT β R −/− mice were observed. Serum NO levels in LT β R −/− animals rose later and were markedly decreased compared to wild-type animals. At the transcriptional level, LT β R −/− animals exhibited a deregulated expression profile of several cytokines known to play a role in activation of innate immunity in T. gondii infection. Importantly, expression of the IFN γ -regulated murine guanylate-binding protein (mGBP) genes was virtually absent in the lungs of LT β R −/− mice. This demonstrates clearly that the LT β R is essential for the induction of a type II IFN-mediated immune response against T. gondii . The pronounced inability to effectively upregulate host defense effector molecules such as GBPs explains the high mortality rates of LT β R −/− animals after T. gondii infection.